(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The following article aims to explore the emerging research agenda in the field of urban security in relation to contemporary threats. In line with a two-fold interpretation of urbanised security, the first part will focus on the growing militarisation of urban spaces. Here, we will look at a number of concepts used by urban geographers and political scientists whose critical stance towards state authorities has dominated the debate. The second part, focusing on urban security, will adopt a more pragmatic position: which elements and functions are vulnerable to natural forces or human activity. A brief analysis of the main risks and threats, as recognised by recent Spanish strategic documents, will also be presented.